2019
DOI: 10.1097/brs.0000000000003101
|View full text |Cite
|
Sign up to set email alerts
|

One-Stage Posterior Multiple-Level Asymmetrical Ponte Osteotomies Versus Single-Level Posterior Vertebral Column Resection for Severe and Rigid Adult Idiopathic Scoliosis

Abstract: Study Design. Retrospective comparative study. Objective. To compare the efficacy and safety of one-stage posterior multiple-level asymmetrical Ponte osteotomies (MAPOs) and single-level posterior vertebral column resection (VCR) for severe and rigid adult idiopathic scoliosis (ADIS). Summary of Background Data. The surgical treatment of severe and rigid ADIS is a demanding and difficult challenge due to its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 23 publications
1
54
0
Order By: Relevance
“…A single-level osteotomy will not affect the flexibility of the spinal segment above and below the osteotomy and cannot achieve 3-dimensional correction of spinal deformity. In a retrospective study, Zhang et al 34 compare the efficacy and safety of posterior multiple-level asymmetrical Ponte osteotomies and posterior vertebral column resection for severe and rigid adult idiopathic scoliosis, and they suggested that multiple asymmetrical Ponte osteotomy is a safe, easy-tooperate, and effective technique that can gain correction outcomes similar to those of VCR, offering the advantages of reduced complications, operation time, and blood loss. Some authors 29 have performed apical Smith Peterson osteotomy for thoracic scoliosis with more than 1008.…”
Section: Discussionmentioning
confidence: 99%
“…A single-level osteotomy will not affect the flexibility of the spinal segment above and below the osteotomy and cannot achieve 3-dimensional correction of spinal deformity. In a retrospective study, Zhang et al 34 compare the efficacy and safety of posterior multiple-level asymmetrical Ponte osteotomies and posterior vertebral column resection for severe and rigid adult idiopathic scoliosis, and they suggested that multiple asymmetrical Ponte osteotomy is a safe, easy-tooperate, and effective technique that can gain correction outcomes similar to those of VCR, offering the advantages of reduced complications, operation time, and blood loss. Some authors 29 have performed apical Smith Peterson osteotomy for thoracic scoliosis with more than 1008.…”
Section: Discussionmentioning
confidence: 99%
“…Schwab et al 32 proposed classification system of spinal osteotomy based on 6 anatomic grades of resection corresponding to the extent of bone resection. The extent of PCO including SPO 2 (grade I) and Ponte osteotomy 33 (grade II) is small, which corrects spinal deformity by removing articular processes. PSO 2 (grade Ⅲ), SRS-Schwab osteotomy 34 (grade Ⅳ), VCR 3 (grade Ⅴ) and multiple VCRs (grade Ⅵ) belong to 3-column osteotomy.…”
Section: Discussionmentioning
confidence: 99%
“…The use of the original Ponte osteotomy for the treatment of rigid AdIS has been well documented in the literature [10][11][12][13]. Clinical and cadaver studies have shown marked segmental flexibility in all three planes produced by Ponte osteotomy [22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this article is to describe the innovative posterior one stage surgical technique summarized with the acronym Hi-PoAD, which consists of simultaneous application of different surgical strategies, all well described individually, as high-density screwing [6][7][8][9], Ponte osteotomies [10][11][12][13], asymmetric rods contouring [14][15][16], direct vertebral rotation (DVR) [17] in the treatment of rigid AdIS (with less than 25% of correction at bending supine radiographs), the complication rate and the clinical and radiographical results obtained at minimum 2 years follow-up (FU) in a cohort of patients over 40 years treated.…”
Section: Introductionmentioning
confidence: 99%